Formaldehyde-Induced Shrinkage of Rat Thymocytes - Hiromi Nakao; Chisato Umebayashi; Mami Nakata; Yasutaka Nishizaki; Katuhiko Noda; Katuhiko Noda; Yasuo Oyama (Elsevier, 2003)
To test the possibility that micromolar formaldehyde, a metabolite of methanol derived from aspartame, exerts cytotoxicity, its effect on rat thymocytes was examined under the in vitro condition using a flow cytometer. Incubation of thymocytes with formaldehyde at 100 μM or more for 24 h significantly increased the populations of shrunken cells and cells with hypodiploid DNA. The peak blood concentration of methanol in human subjects administered abuse doses of aspartame has been reported to exceed 2 mg/dL (625 μM). It would increase the population of thymocytes undergoing apoptosis if formaldehyde at 100 μM or more appears in the blood after administration of aspartame.